2014
DOI: 10.1017/s1049023x14001125
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Cold, Wind, and Moisture Protection of Different Coverings for Prehospital Maritime Transportation–A Thermal Manikin and Human Study

Abstract: The selected optimum rescue bag consisted of insulating and water-resistant layers providing sufficient protection against cold, wind, and water splashes during prehospital transportation lasting 30 minutes in the uncovered portion of a motor boat. The minimum thermal insulation for safe maritime transportation (30 minutes) is 0.46 m²K/W at a temperature of -5°C and a wind speed of 10 m/s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
1
9
0
4
Order By: Relevance
“…In a study by Jussila et al, it was shown that choosing the optimal rescue bag made of water-resistant layers could provide adequate protection against cold, wind, and splash of water during the pre-hospital transfer. This finding is consistent with the results of our study (10). A systematic review was conducted by Haverkamp et al (12) regarding current hypothermia treatment and their efficacy in pre-hospital hypothermia management.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In a study by Jussila et al, it was shown that choosing the optimal rescue bag made of water-resistant layers could provide adequate protection against cold, wind, and splash of water during the pre-hospital transfer. This finding is consistent with the results of our study (10). A systematic review was conducted by Haverkamp et al (12) regarding current hypothermia treatment and their efficacy in pre-hospital hypothermia management.…”
Section: Discussionsupporting
confidence: 93%
“…In many cases, where the patient can be transferred quickly to a care facility, the passive rewarming approach is all that has been mentioned in the pre-hospital setting. Many studies have been performed to evaluate and compare different materials and products (7)(8)(9)(10)(11). However, recommendations concerning which items should be used in the field are often based on experience instead of scientific evidence.…”
mentioning
confidence: 99%
“…Thermal insulation of the clothing ensembles were measured by using an aluminum thermal manikin consisting of 20 segments in a climate chamber 14 ) . The measurements were divided into two parts: dry resultant effective thermal insulation with walking thermal manikin (I cler ) according to the standard for cold protective clothing 13 ) and effect of wind on heat loss with standing thermal manikin.…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7]9,[30][31][32] Most of the human studies had a small number of subjects. 9,[30][31][32] Because the subjects were not hypothermic, skin surface temperatures were likely higher than they would have been in hypothermic subjects. Individual studies do not describe exactly how the reflective foils were placed, limiting the ability to compare results among studies.…”
Section: Clinical Studiesmentioning
confidence: 99%